Transforming India : social and political dynamics of democracy - Frankel,Francine R.(Editor) Hasan,Soya(Editor) Bhargava,Rajeev(Editor) Arora,Balveer(Editor) (Oxford University Press, 2000)
Revision of papers originally presented at a conference held at India International Centre in Nov. 1997.